Peritoneal Dialysis Failure and its Impact on Holistic Kidney Care: A Case Report - Jeffrey Yuk Chiu Yip MNSc, RN (HK) (SAGE Publishing, 2021)
Introduction Peritonitis remains the primary cause of treatment failure among patients with end-stage kidney disease on continuous ambulatory peritoneal dialysis. However, detailed case analyses illustrating the application of current research in clinical practice remain scant. This case report aimed to elucidate the roles of dialysis nurses in a hospital setting in the management of a 62-year-old male patient with a history of kidney failure secondary to amyloidosis. Case Presentation The patient was diagnosed with continuous ambulatory peritoneal dialysis-associated peritonitis. Management and Outcomes Dialysis nurses applied evidence-based practices in the management of the patient's exit-site infection, imbalanced nutrition, and psychosocial concerns. The patient was discharged after 7 days, with a comprehensive treatment regimen, including an individualized peritoneal dialysis protocol adjusted to his daily schedules, education on self-care techniques, and continual nutritional management to prevent recurrence and improve his overall health. This case report shows that admissions for continuous ambulatory peritoneal dialysis-associated peritonitis require evidence-based nursing interventions specific to, and geared toward, each patient's prioritized health problems. Discussion Peritonitis cases are preventable with appropriate nursing interventions that can lower the chance of treatment failure and long-term impact caused by an abrupt switch to hemodialysis. To successfully manage patients with continuous ambulatory peritoneal dialysis-associated peritonitis, dialysis nurses should appreciate the intricacies of the analyses underpinning their professional practices in promoting the patient's self-care techniques.